2022
DOI: 10.3390/nu14245268
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Role of Ferroptosis in Testicular Function

Abstract: Iron is an important metal element involved in the regulation of male reproductive functions and has dual effects on testicular tissue. A moderate iron content is necessary to maintain testosterone synthesis and spermatogenesis. Iron overload can lead to male reproductive dysfunction by triggering testicular oxidative stress, lipid peroxidation, and even testicular ferroptosis. Ferroptosis is an iron-dependent form of cell death that is characterized by iron overload, lipid peroxidation, mitochondrial damage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Moreover, abnormal protein levels of GPX4, COX2, ACSL4, NCOA4, FTH1, as well as alterations in the content of GSH and NADPH, serve as biomarkers of ferroptosis. Presently, a connection between ferroptosis and male reproduction disorder has been established 39 . In fact, some studies have reported that the induction of testicular oxidative stress leading to ferroptosis by substances such as arsenite, copper, and PM2.5 particles 33 , 40 , 41 , while Di (2-ethylhexyl) phthalate has been shown to induce ferroptosis via HIF-1α/HO-1 signaling pathway and transferrin receptor 1 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, abnormal protein levels of GPX4, COX2, ACSL4, NCOA4, FTH1, as well as alterations in the content of GSH and NADPH, serve as biomarkers of ferroptosis. Presently, a connection between ferroptosis and male reproduction disorder has been established 39 . In fact, some studies have reported that the induction of testicular oxidative stress leading to ferroptosis by substances such as arsenite, copper, and PM2.5 particles 33 , 40 , 41 , while Di (2-ethylhexyl) phthalate has been shown to induce ferroptosis via HIF-1α/HO-1 signaling pathway and transferrin receptor 1 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione (GSH) is a tripeptide consisting of glycine, cysteine, and glutamic acid-containing Y-amido-hexapeptide and sulfhydryl groups, which is an important antioxidant [ 40 , 41 ]. GSH functions intracellularly as a vital substrate for GPX4 [ 42 ].…”
Section: Regulation Of Ferroptosismentioning
confidence: 99%
“…Including 0.2 mg/kg SeMet in feed has been shown to effectively reduce ROS and MDA levels and enhance SOD and GSH-Px activity. 65,66 Se can also alleviate the inflammatory response of the jejunum and enhance ZO-1 and occludin expression to preserve the integrity of the intestinal barrier. Se has demonstrated strong antioxidant properties to protect against mycotoxins.…”
Section: Advances In Alleviating the Enterotoxicity Of T-2 Toxinmentioning
confidence: 99%
“…The results showed that the ROS level in the small intestine was markedly elevated and that antioxidant activity and the expression of occludin and ZO-1 were considerably decreased. Including 0.2 mg/kg SeMet in feed has been shown to effectively reduce ROS and MDA levels and enhance SOD and GSH-Px activity. , Se can also alleviate the inflammatory response of the jejunum and enhance ZO-1 and occludin expression to preserve the integrity of the intestinal barrier. Se has demonstrated strong antioxidant properties to protect against mycotoxins.…”
Section: Advances In Alleviating the Enterotoxicity Of T-2 Toxinmentioning
confidence: 99%